2015
DOI: 10.1016/j.physletb.2015.05.033
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of dijet kT in p–Pb collisions at sNN

Abstract: A measurement of dijet correlations in p-Pb collisions at √ s NN = 5.02 TeV with the ALICE detector is presented. Jets are reconstructed from charged particles measured in the central tracking detectors and neutral energy deposited in the electromagnetic calorimeter. The transverse momentum of the full jet (clustered from charged and neutral constituents) and charged jet (clustered from charged particles only) is corrected event-by-event for the contribution of the underlying event, while corrections for under… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…This conclusion is supported by a different approach, where events are ordered based on the zero-degree energy of slow neutrons produced in the collision on the Pb-going side, and an estimate of N coll from a data-driven approach inspired by the wounded nucleon model [121]. Furthermore, no significant nuclear modification has been seen in (charged) jet spectra [152], D-meson yields [148] nor dijet k T [153] at mid-rapidity either. While direct jet quenching [154] has not been observed, possible non-zero v 2 values of about 5% at p T up to 10 GeV/c albeit with rather large uncertainty have been reported [64].…”
Section: Results From Ppb Collisions At High Multiplicitymentioning
confidence: 90%
“…This conclusion is supported by a different approach, where events are ordered based on the zero-degree energy of slow neutrons produced in the collision on the Pb-going side, and an estimate of N coll from a data-driven approach inspired by the wounded nucleon model [121]. Furthermore, no significant nuclear modification has been seen in (charged) jet spectra [152], D-meson yields [148] nor dijet k T [153] at mid-rapidity either. While direct jet quenching [154] has not been observed, possible non-zero v 2 values of about 5% at p T up to 10 GeV/c albeit with rather large uncertainty have been reported [64].…”
Section: Results From Ppb Collisions At High Multiplicitymentioning
confidence: 90%
“…In fact, until a few years ago, most nPDF analyses [17][18][19][20][21][22] were largely based on fixed-target DIS structure functions in lepton-nucleus scattering (with kinematic coverage restricted to x ∼ > 0.01) supplemented by some Drell-Yan cross-sections. A major improvement in this respect has been the recent availability of data on hard-scattering cross-sections from proton-lead collisions at the LHC, with processes ranging from jet [23][24][25][26][27] and electroweak boson production [28][29][30][31][32], to heavy quark production [33][34][35][36][37][38][39][40] among several others. Indeed, measurements of hard probes in p+Pb collisions provide useful information to constrain the nPDFs, as was demonstrated by a few recent studies [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…Additional measurements that go beyond single inclusive hadrons may be able to shed further light on this phenomenon in p + A collisions. For example, dijet measurements in the kinematic regime of the Cronin effect have shown that the initial-state partonic transverse momentum is a function of the nucleus size [21], which was not observed at large jet transverse momentum [22].…”
Section: Introductionmentioning
confidence: 99%